Ghana : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2012)
This Joint Staff Advisory Note of the Poverty Reduction Strategy Paper (PRSP) on Ghana reviews the Ghana Shared Growth and Development Agenda (GSGDA) for the period 2010-13. The GSGDA comprises three volumes: the policy framework, the costing framework, and the monitoring and evaluation framework; and follows Ghana Poverty Reduction Strategy I and II (GPRS-I and GPRS-II). IMF staff finds the underlying sector development plans compelling and well considered. However, important risks to implementation remain, which could reduce Ghana's ability to meet the GSGDA objectives.